Helicobacter pylori Infection Acts as an Independent Risk Factor for Intracranial Atherosclerosis in Women Less Than 60 Years Old - Guo, Yinjie; Xu, Canxia; Zhang, Linfang; Chen, Zhiheng; Xia, Xiujuan (Frontiers in Cardiovascular Medicine, 2022)
Background: Studies show inconsistent results regarding the relationship between Helicobacter pylori (H. pylori) infection and stroke. The present study assessed a potential association between H. pylori infection and an important risk factor for stroke, intracranial atherosclerosis. Methods: 15,798 subjects with transcranial Doppler and 13C-urea breath test were enrolled from March 2012 to March 2017. Intracranial atherosclerosis was further measured using intracranial carotid artery calcification (ICAC) on past or recent Head CT, and 14,084 subjects were ultimately included in the study. Baseline demographics, atherosclerosis risk factors, and laboratory results were investigated. Since endothelial dysfunction is critical to the development of atherosclerosis, the role of H. pylori in migration, tube formation, and proliferation of human brain microvascular endothelial cells (HBMEC) was assessed in vitro. Results: The intracranial atherosclerosis group had a higher proportion of females and a greater rate of H. pylori infection than those without intracranial atherosclerosis. H. pylori infection was significantly more common in females with intracranial atherosclerosis than males. In addition, the incidence of intracranial atherosclerosis was significantly higher in females with H. pylori infection than uninfected females (53.8% vs. 46.4%, p<0.001). In an adjusted model, H. pylori was shown to be an independent risk factor for intracranial atherosclerosis in females ≤60 years of age (OR=2.261, 95%CI=1.839-2.780, p<0.001). Serum exosomes from patients with H. pylori infection had significantly reduced brain endothelial cell migration, tube formation, and proliferation in vitro. Conclusion: H. pylori infection may be an important independent risk factor for intracranial atherosclerosis in females ≤60 years of age.